Applied Multitemporal Image and Geography Information System to Analyze Region Potential in Part of Slump of Jebres Subdistrict in Surakarta - Rindarjono, Moh. Gamal (Forum Geografi, 2002)
This research is aimed at detecting the areas having potential to be the slums by looking at the decrease of population index and physical environment from year to year. In this way, a model of analysis for the area with the potential of being slummed can be resulted.The research was conducted in some parts of Jebres Subdistrict in Surakarta Municipality by employing qualitative method approach. There were two types of data used in this research. The ï¬rst were prime data inform of black and white Panchromatic aerial photographs with the scale of 1 :5 O00 at the year of 1982, and small format colorful anchromatic aerial photographs at the year of 1992. The second were secondary data related to the population condition i.e. demography, economy, health, social and culture, as well as physical environment covering water and land for 20 years (1982 j 2000).All the data in this research were analyzed by Geographical Inï¬ormation Systems at arc Info. The final result of the research showed that based on the 1982 black and white Panchromatic aerial photographs, slum areas did not exist at all. Meanwhile, based on the 1992 small format colorful Panchromatic aerial photographs with the scale of 1:5 000, 140.882 hectares of slum areas were found at jagalan and Gandekan Villages. Overlay from the maps of quality development in dwelling area and the decrease in environment index produced a map showing the area with the potential of being slummed covering 240.14 Hectares.